Diagnostic and Clinical Significance of Serum Levels of D-Lactate and Diamine Oxidase in Patients with Crohn’s Disease - Jierui Cai; Hong Chen; Meiling Weng; Shuyu Jiang; Jie Gao (Gastroenterology Research and Practice)
Background. Crohn’s disease (CD) is a chronic intestinal inflammatory disease. An ideal laboratory marker that can predict the prognosis in terms of relapse of the disease is clinically desirable. Methods. A total of 59 CD patients were enrolled in this study. Enzyme-Linked Immunosorbent Assay (ELISA) was used to quantitatively detect the content of D-lactate (D-LA) and the diamine oxidase (DAO) levels in sera obtained from patients and 28 healthy controls. The correlation between these two biomarkers and disease activity scores was assessed. In addition, the ROC curve was used to evaluate the diagnostic accuracy of these two biomarkers. Results. The levels of D-LA in the serum of CD patients in the active stage and remission stage were 16.08±4.8 mg/L and 11.16±3.17 mg/L, respectively, and the difference was statistically significant (t=4.67, P<0.001). DAO levels were significantly higher in patients with the active stage compared to controls. The levels of D-LA and DAO in CD patients were positively correlated with the disease activity (r=0.68 and 0.53, respectively, P<0.05). The area under the ROC curve (AUC) when CD activity was diagnosed with D-LA and DAO alone was 0.815 and 0.748, respectively. The diagnostic efficacy of the two biomarkers was not significantly different from that of the erythrocyte sedimentation (ESR) and hypersensitive C-reactive protein (CRP) (P>0.05). However, the area under the curve was 0.861 (0.746, 0.937) when the diagnosis was performed using a combination of D-LA, DAO, CRP, and ESR, which was significantly higher than when CRP or ESR were tested alone (P<0.05). Conclusions. D-LA and DAO have a good prognostic value for CD activity. Rational combined use of biomarkers can significantly improve the diagnostic efficiency.